PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MEMBANGUN SEKOLAH UNGGUL BERBASIS NILAI-NILAI ISLAM - Rosa Melinda; Istanto, Istanto (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2025)
This study aims to describe the principal’s leadership in realizing an excellent school at SMP IT MTA Karanganyar and to identify the supporting factors. Using a qualitative approach with a phenomenological method, data were collected through observation, in-depth interviews, and document analysis. The results show that the principal applies a transformational leadership style that is visionary, inspiring, and participatory, focusing on strengthening four flagship programs: Tahsin (Qur’anic reading), Tahfidz (Qur’anic memorization), Character Building, and ICT-Based Learning. The success of these programs is supported by the active involvement of teachers, the principal’s exemplary behavior, adequate facilities, parental support, and a structured system of evaluation and appreciation. Challenges such as the diverse backgrounds of students are addressed through personalized approaches and continuous mentoring. These findings emphasize that effective school leadership plays a central role in fostering a religious, excellent, and technologically adaptive school culture.